Industrial Seawater Cooling Systems under Threat from the Invasive Green Mussel Perna viridis - Vayalam P. Venugopalan (Universitas Gadjah Mada, 2018)
The green mussel Perna viridis, native to the Asia-Pacific region, has been introduced to other regions such as the Caribbean, Japan and North and South America. It is a large, commercially important species, widely cultivated and harvested in Southeast Asia, but is also considered an invasive species elsewhere, capable of replacing native species. As a fouling organism in intake systems of coastal power plants, it causes flow blockage and loss of cooling efficiency. Mussel colonization during peak settlement season can exceed 35,000 individuals/m2 and biomass can exceed 100 kg/m2. They can withstand wide fluctuations in temperature and salinity. Previous work has shown that a conventional biofouling control measure such as chlorination is not very effective against these bivalves, unless applied continuously for extended periods of time. We require more efficient, environmentally compatible methods of biofouling control. The paper discusses these issues in the context of the perceived invasion potential of P. viridis.